2002
DOI: 10.7326/0003-4819-136-9-200205070-00008
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Immunity to Diphtheria and Tetanus in the United States

Abstract: A substantial proportion of adults in the United States do not have antibody levels that are protective against diphtheria and tetanus. In addition, although the recommended vaccine is a combination of tetanus and diphtheria, only 63% of adults with protective antibody to tetanus also had protective antibody to diphtheria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(116 citation statements)
references
References 13 publications
9
100
2
5
Order By: Relevance
“…However, adolescents older than 15 years had higher antibody levels than those younger than 15 for tetanus (0.972 vs 0.390, respec- munity, more individuals with up-to-date vaccination cards were found to be fully protected against tetanus. These findings confirm that, as age progresses, a person's susceptibility to tetanus and diphtheria increases if booster doses are omitted (8,9,14,(16)(17)(18)(19).…”
supporting
confidence: 74%
“…However, adolescents older than 15 years had higher antibody levels than those younger than 15 for tetanus (0.972 vs 0.390, respec- munity, more individuals with up-to-date vaccination cards were found to be fully protected against tetanus. These findings confirm that, as age progresses, a person's susceptibility to tetanus and diphtheria increases if booster doses are omitted (8,9,14,(16)(17)(18)(19).…”
supporting
confidence: 74%
“…They also correlate with data from different studies showing that many American and European subjects over 50 years old do not have sera protective concentrations of anti-DT antibodies. [14][15][16] Despite the fact that a second booster was not recommended in France before 1998, we observed that 74% of the subjects had received more than one pertussis booster. Anti-PT antibody of ≥125 IU/mL suggesting a very recent infection were found in 7.6% of the study population, and this percentage was higher (13.4%) in those aged 18-29 years (mean age, 23 years; 95% CI, 21.27-24.75).…”
Section: Resultsmentioning
confidence: 85%
“…Serologic and survey data indicate that US adults are undervaccinated with Td, and that rates of coverage decline with increasing age. 11,12 In addition, studies of adult vaccination practices have found specialty-based differences in influenza and pneumococcal immunization practices; 13,14 similar differences may exist for Td, and potentially for Tdap vaccine as well.…”
Section: Introductionmentioning
confidence: 99%